(untitled) (European Journal of Interdisciplinary Research and Development, 2023)
The article analyses tendencies of changes of main macroeconomic rations of social-economic development of Uzbekistan. Econometric models for forecasting of number of population, GDP volumes and other rations of economic growth of the country are designed. The article also proposes forecasted ways of changes in macroeconomic rations in the future.